The end of faith religion, terror, and the future of reason - Harris, Sam 1967- (Simon & Schuster UK Ltd, 2006)
A startling analysis of the clash of faith and reason in today's world, this historical tour of mankind's willingness to suspend reason in favor of religious beliefs, even when those beliefs are used to justify atrocities, asserts that in the shadow of weapons of mass destruction, we can not expect to survive our religious differences indefinitely. Most controversially, argues that moderate lip service to religion only blinds us to the real perils of fundamentalism. Harris also draws on new evidence from neuroscience and insights from philosophy to explore spirituality as a biological, brain-based need, and invokes that need in taking a secular humanistic approach to solving the problems of this world.